2012
DOI: 10.1039/c2sm25604e
|View full text |Cite|
|
Sign up to set email alerts
|

Phase behaviour and complex coacervation of aqueous polypeptide solutions

Abstract: Mixing of oppositely charged polyelectrolytes in aqueous solutions may result in the formation of polyelectrolyte complexes (PEC). Phase separation and complex coacervation of polypeptides are investigated in this study. Polypeptides have identical backbones and differ only in their charged side groups, making them attractive model systems for this work. All experiments are conducted using equal chain lengths of polycation and polyanion in order to isolate and highlight effects of the interactions of the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
404
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(434 citation statements)
references
References 35 publications
23
404
1
Order By: Relevance
“…In particular, they did not observe a single-phase solution for ( ) ≤ 5 M for the pH = 5 case, which bears similarity to the low pH behavior we observe for the PAA-PDMAEMA-KCl and PAA-PDADMAC-KCl systems. However, Priftis and Tirrell [9] observed a somewhat different trend in their experiments on polypeptide complexation. They observed that the critical salt concentration always increased with an increase in degree of dissociation of polyelectrolytes, as we find theoretically in the absence of hydrophobicity effects ( = = 0) in Figure 4a.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, they did not observe a single-phase solution for ( ) ≤ 5 M for the pH = 5 case, which bears similarity to the low pH behavior we observe for the PAA-PDMAEMA-KCl and PAA-PDADMAC-KCl systems. However, Priftis and Tirrell [9] observed a somewhat different trend in their experiments on polypeptide complexation. They observed that the critical salt concentration always increased with an increase in degree of dissociation of polyelectrolytes, as we find theoretically in the absence of hydrophobicity effects ( = = 0) in Figure 4a.…”
Section: Resultsmentioning
confidence: 94%
“…They observed that the critical salt concentration always increased with an increase in degree of dissociation of polyelectrolytes, as we find theoretically in the absence of hydrophobicity effects ( = = 0) in Figure 4a. Further, all these studies [2,3,9] have reported a precipitate → coacervate transition with increase in salt concentration. The high critical salt concentrations at low pH observed in our experiments also shows resemblance to the increased stability of multilayer films containing weak polycarboxylic acids at low pH observed in an earlier experimental study [45], where the critical salt concentration required to dissolve the multilayers was found to increase dramatically at low pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ions released in the solution decrease the Debye length and reduce the ability of the oppositely charged polypeptides to interact (Weinbreck et al, 2003, Priftis & Tirrell, 2012.…”
Section: Effect Of Total Biopolymer Concentrationmentioning
confidence: 99%
“…The qualitative nature of turbidity-style measurements allows a phenomenological characterization of coacervate phase behavior, rather than a more direct quantification of the binodal phase space [8,15,71,[73][74][75][76][77]83,88,[91][92][93]104,105,108,112,114,. Typical characterization experiments include evaluation of the stoichiometric ratio of polycation to polyanion, the effect of increasing salt concentration, and the effect of variable pH.…”
Section: Connecting Coacervate Phase Behavior With Materials Dynamicsmentioning
confidence: 99%